Factors affecting the rate of immunosuppression development in children with HIV infection - V. B. Denisenko (Žurnal Infektologii, 2022)
The purpose is improving the prediction of the immune status dynamics in children with HIV infection, taking into account independent predictors.Materials and methods. Clinical, immunological, molecular genetic examination of 91 pairs «HIV-infected mother – child with HIV infection» was carried out. All children did not receive antiretroviral therapy. The age of children at the time of immunosuppression development was determined. The criterion for immunosuppression at the age of less than 1 year was a decrease in the number of CD4 lymphocytes to 30–35% (1,0–1,5 × 109  / l), at the age of 1–5 years – to 25–30% (0,75–0,999 × 109  / l), over the age of 5 years – up to 20–25% (0,35–0,499 × 109  / l). To determine the factors affecting the rate of development of immunosuppression, we used mathematical models for analyzing the time to event (survival) and proportional Cox intensities.Results. All children aged 9–54 months (median 22 months, interquartile interval 13-42 months) developed immunosuppression. Using a mathematical model of proportional Cox intensities, we tested anamnestic, clinical and laboratory parameters characterizing the state of health, HIV status of the mother, the course of pregnancy and childbirth, chemoprophylaxis of vertical HIV transmission, pathology of the neonatal period in children. Statistical significance in the multivariate model was demonstrated by the indicators «Lack of HIV vertical transmission chemoprophylaxis» (odds ratio 2,5; 95% confidence interval 1,4–7,7; P = 0,033) and «Congenital herpesvirus infection» (odds ratio 3,0; 95% confidence interval 1,3–6,9; P < 0,001).Conclusion. All children with HIV infection quickly developed immunosuppression. The independent factors influencing the timing of the immunosuppression development were the lack of HIV vertical transmission chemoprophylaxis and the congenital herpesvirus infection. The results of the study make it possible to recommend expanding the coverage of HIV-infected pregnant women and their children with three-stage vertical HIV transmission chemoprophylaxis and improving measures for the diagnosis and treatment of congenital herpesvirus infections.